2000
DOI: 10.1021/om990609c
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Redox Mechanism for the Reaction of “Cation-like” Zirconocene Silyl Complexes with Silanes

Abstract: A kinetic study of the photochemical reaction of [Cp 2 Zr(µ-SiH 2 Ph)] 2 2+ 2[BBu n (C 6 F 5 ) 4-n ] -(1) with PhCH 2 SiH 3 to give the analogous PhCH 2 SiH 2 complex 2 was carried out using a combination of NMR and EPR spectroscopy to follow the rates of disappearance of reactants and the appearance of intermediates and products. The paramagnetic intermediate [Cp 2 Zr III ] + [BBu n (C 6 F 5 ) 4-n ] -(3) is produced with a quantum efficiency of 0.96 ( 0.16 on irradiation of 1 with light having λ < 450 nm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The reaction of Pt(PEt 3 ) 4 with PhSSiCl 3 provided trans-(Et 3 P) 2 Pt(SPh)(SiCl 3 ) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in >95% by NMR. 554 Although not common, Pt(0) appeared to catalyze the addition of Si-S bonds to alkynes when a mixture of (ArS) 2 and Si 2 Cl 6 was heated with a terminal alkyne in the presence of (Ph 3 P) 2 Pt(CH 2 dCH 2 ).…”
Section: Si-el (El ) Sn B S)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of Pt(PEt 3 ) 4 with PhSSiCl 3 provided trans-(Et 3 P) 2 Pt(SPh)(SiCl 3 ) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in >95% by NMR. 554 Although not common, Pt(0) appeared to catalyze the addition of Si-S bonds to alkynes when a mixture of (ArS) 2 and Si 2 Cl 6 was heated with a terminal alkyne in the presence of (Ph 3 P) 2 Pt(CH 2 dCH 2 ).…”
Section: Si-el (El ) Sn B S)mentioning
confidence: 99%
“…147a 3-17 and 3-18 are isomers that differ in position of the Me 3 P and Cl ligands. 30 Additional derivative made with HSiClMePh and another made with HSiMe 2 Cl and with PhMe 2 P replacing PMe 3 (X-ray). 32a 31 X-ray structure was only of sufficient quality to establish overall geometry.…”
mentioning
confidence: 99%
“…An emerging strategy for dealing with the above challenges involves the use of Lewis acid-based cocatalysts in conjunction with transition- metal-based catalysts. Thus, Harrod and Dioumaev have reported that the presence of B(C 6 F 5 ) 3 in reactions catalyzed by the Cp 2 ZrCl 2 /BuLi system gives (PhSiH) n with higher M w . Tilley et al have also reported that cation-like species generated by the action of B(C 6 F 5 ) 3 or [HNR 3 ][BAr 4 ] on metallocenes display higher reactivities toward silanes;5d these authors caution us, however, that the use of these cocatalysts does not always improve the chain growth process and in some cases leads to redistribution reactions involving Si−C bond cleavage …”
Section: Introductionmentioning
confidence: 99%
“…Such effects have ample precedent . The depressed activity as silane concentration is increased is reasonably ascribed to the Lewis basicity of this reagent. ,8b Microstructural analysis of the polymeric product reveals n -hexyl-SiH 2 -capped polyethylene [ 1 H NMR in C 2 D 2 Cl 4 , at 120 °C: δ 3.72 ( SiH 2 ); 13 C NMR in C 2 D 2 Cl 4 , at 120 °C: δ 9.09 ( CH 2 SiH 2 ); 29 Si NMR in C 2 D 2 Cl 4 , at 120 °C: δ −29.8 ( SiH 2 ); IR in a KBr pellet: 2020 cm -1 (ν Si - H )), which compares favorably with an authentic capped polyethylene sample produced using n -hexyl-SiH 3 and an effective homogeneous polymerization/chain transfer catalyst, [Me 2 Si(Me 4 C 5 ) 2 ]SmCH(SiMe 3 ) 2 2b. It can be seen from the 1 H NMR spectrum of the polyethylene produced from SiO 2 /MAO/ 1 in the presence of n -hexyl-SiH 3 (Figure ) that the combined intensity of the CH 3 groups (d + h) at the saturated chain end, overlapping with the n -hexylsilyl CH 3 signal, is larger than the C H 3 :C H 2 Si:Si H 2 intensity ratio of 6.0:4.0:2.0 expected from Scheme .…”
mentioning
confidence: 98%
“…NMR and GC/MS analyses of the methanol-soluble polymerization reaction byproducts isolated from workup reveal linear and cyclic silane coupling products and n -alkanes having exclusively even carbon numbers between 14 and 26. It is well-known that cationic organo-group 4 complexes catalyze dehydrogenative silane coupling to produce polysilane oligomers (Scheme , cycle B) . It is reasonable that the H 2 byproduct of this reaction functions as a chain transfer agent, resulting in saturated polyethylene chain ends (Scheme , cycle A).…”
mentioning
confidence: 99%